The Relationship Between Knowledge Level And Cold Cough Self-Medication Behavior In Students Of The University Of Singaperbangsa Karawang - Hidayat, Sofianti; Mally Ghinan Sholih; Munir Alinu Mulki (Jurnal EduHealth, 2024)
Self-medication for coughing up a cold is common, especially among students. Factors such as stress, lack of sleep, unhealthy diet, and poor hygiene can increase the risk of developing a cold cough. The availability of drugs on the market significantly facilitates students to self-medicate the symptoms of the disease they experience, because it is considered faster, economical, and practical without the need for medical consultation. This study aims to determine the relationship between respondents' characteristics on the level of knowledge and self-medication behavior of cold cough and determine the relationship between the level of knowledge on cold cough self-medication behavior in active students of Singaperbangsa University Karawang. The method used was descriptive analytic with Cross Sectional approach and involved 390 randomly selected respondents. The study was conducted from February to March 2024. The results of this study showed that 59.5% of respondents had good knowledge of cold cough self-medication, and 40.5% had poor knowledge. Then the self-medication behavior of cold cough showed that 58.2% of respondents had good behavior, and 41.8% had bad behavior. There is a relationship between the characteristics of respondents to the level of knowledge and self-medication behavior of cold cough, namely faculty with a p-value knowledge level of 0.004 < 0.050, and there is a relationship between faculty and behavior obtained p-value of 0.005 < 0.050. The results of the study The Relationship of Knowledge Level to Behavior was tested using a chi-square p-value test of 0.001 < 0.050. It can be concluded that there is a significant relationship between the level of knowledge and the self-medication behavior of cold cough.